2013
DOI: 10.1007/s00405-013-2729-0
|View full text |Cite
|
Sign up to set email alerts
|

Are computed tomography and densitometric measurements useful in otosclerosis with mixed hearing loss? A retrospective clinical study

Abstract: The objective of the study was to investigate the relationship between extent of otosclerotic foci and audiological findings in otosclerotic patients with mixed hearing loss using high-resolution computed tomography (HRCT) and also to measure the density of bony labyrinth in otosclerotic patients and compared with control group. This was a retrospective study. Twenty-five patients with clinical otosclerosis and mixed hearing loss were included in the study. The average threshold of air-bone conductions (AC, BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 12 publications
0
27
0
1
Order By: Relevance
“…Prior studies have examined densitometry measurements on HRCT and found significantly lower density in active otospongiosis compared with control ears. [24][25][26] Moreover, hypodensity at the fissula ante fenestram has been shown to correlate with a conductive-component of hearing loss in the low frequencies. [24][25][26] Tringali and colleagues also found density measurements at the fissula ante fenestram were significantly lower in patients with otosclerosis compared with the control group.…”
Section: Density Measurementsmentioning
confidence: 99%
“…Prior studies have examined densitometry measurements on HRCT and found significantly lower density in active otospongiosis compared with control ears. [24][25][26] Moreover, hypodensity at the fissula ante fenestram has been shown to correlate with a conductive-component of hearing loss in the low frequencies. [24][25][26] Tringali and colleagues also found density measurements at the fissula ante fenestram were significantly lower in patients with otosclerosis compared with the control group.…”
Section: Density Measurementsmentioning
confidence: 99%
“…There are many studies in the literature concerning densitometric measurements of the labyrinth together with the temporal bone in otosclerosis using high‐resolution computed tomography (HRCT), which provides a quantitative evaluation of the cochlear capsule density . Densitometry using HRCT has also been reported to provide information about the otospongiotic or sclerotic stage of the otosclerotic foci and has been shown to be an effective method of diagnosis of otosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…AC and BC thresholds were worse in cases of extensive otosclerotic foci, as declared by Marx et al [18] . Kultar et al [19] concluded that there was no significant relationship between early stage (fenestral, focal) and hearing thresholds, but there was a significant relationship in advanced (diffuse) stage. In our study, we were unable to find any significant relationship between the size of otosclerotic lesions in any of the CT grades and hearing thresholds (BC and ABG).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to measure the CT density of otosclerotic lesions at the FAF region, as it is the most commonly affected area in otosclerosis [20] and because lower density in this region often appears in otosclerosis [19,21] .…”
Section: Discussionmentioning
confidence: 99%